Academician Mikhail Alexandrovich D’yakonov - the Chairman of the Permanent Library Commission of the Academy of Sciences - E. D. D’Yachenko; N. N. Elkina (Библиосфера, 2016)
Based on archival materials and published sources the authors determine the Academician M. A. Dyakonov role as the Chairman of the Permanent Library Commission in the Russian Academy of Sciences (1915-1919) and simultaneously the Director of the Library of the Academy of Sciences (1916-1919).